`Doing` competitive swimming: Exploring the skilled practices of the competitive swimming lifeworld - McNarry, G.; Allen-Collinson, J.; Evans, A. B. (International Review for the Sociology of Sport, 2021)
Despite a developing literature on various facets of sporting embodiment, there is currently a research lacuna with regard to in-depth analyses of actually `doing` sporting activities within specific physical cultures. In this article, we address that gap by drawing on a developing theoretical literature in sociological phenomenology to investigate a particular physical-cultural domain. Here, we present and analyse data from an ethnographic study of competitive swimmers undertaken in the UK. Responding to calls to explore the domain of `body pedagogics`, we investigate the embodied work involved in the skilled practice of `doing` and learning how to `do` competitive swimming. This embodied work plays a key part in the swimmers` ability to inhabit the competitive swimming lifeworld. In the analysis, we highlight how the acquisition and `habituation` of these body techniques and skilled behaviours are not achieved simply through the repetitive rehearsal of coherent movements over time. These processes are complex, demanding practical experimentation, discovery and the ability to adapt constantly to changes in the environment and the swimmer`s own corporeality.